Guru Madrasah Sebagai Self Control Peserta Didik Usia Remaja - Salmah (Adz-Zikr : Jurnal Pendidikan Agama Islam, 2016)
Madrasa teachers are people who master the science of religion while also being able to transfer knowledge, internalize, and practice (implementation); able to prepare students to be able to grow and develop their intelligence and creativity for the benefit of themselves and their communities; able to be a model or central of self-identification and consultant for students; have information sensitivity, intellectual and spiritual norms and are able to develop talents, interests, and abilities to prepare students who are responsible for building a civilization that is blessed by God. Self Control is the ability of individuals to control, guide, manage, and regulate their behavior in dealing with stimuli from outside their environment or satisfying immediate needs to achieve better results in the future. Students who reach the age of adolescence last approximately 13 years to 16 years or 17 years. The end of adolescence between the ages of 16 to 18 years is a transition period when individuals grow from childhood to maturity. Madrasa teachers have a greater responsibility in educating their students. As a teacher is not only limited to conveying religious knowledge but also must be able to form students who can control themselves (self-control) at the age of adolescence to become creatures of noble character. and can practice the values ​​of Islamic teachings.